PREDICTION OF EXPOSURE CONDITIONS IN VICINITY OF UMTS BASE STATION ANTENNAS - Wójcik, D. (Science and Transport Progress, 2007)
The rapid diffusion of wireless telecommunications has focused attention on potential risks for human health due to the exposure to electromagnetic (EM) fields. In context of cellular telephony the problem should be considered in two different aspects: possible health hazard due to hand-held phone devices or due to base station antennas, which this paper will be devoted to. To evaluate exposure condition in vicinity of Universal Mobile Telecommunication System (UMTS) base station antenna, the method based on the replacement of panel antenna with a discrete linear array and combined with the geometrical optics and uniform theory of diffraction